Characterization, Classification and its Impact on Yield and Quality of Tamarind in Marathwada Region, Maharashtra - P.H. Vaidya (Journal of the Indian Society of Soil Science, 2023)
Knowledge of soil properties is significant for making decisions concerning sustainable production and land-use. Fourteen typical pedons of tamarind orchards (variety Prathisthan) from different landforms of the Marathwada region of Maharashtra were surveyed, characterized and classified based on morphological, physical and chemical properties of the soil. The results revealed that variation in morphological, physical and chemical properties of the soils with landform. Tamarind growing soils were very shallow to very deep (19-150 cm), soil colour varies from black to dark grayish brown in colour (10YR 2.5/1 to 10YR 7/2), deep soils were located in low lying area and dominant soil colour is grayish brown (10YR 3/2) in surface horizon. The bulk density of soils ranged from 1.27 to 1.62 Mg m-3 and it increased with soil depth while saturated hydraulic conductivity varied from 2.12 to 29.8 cm h-1 and clay content and plant available water capacity (PAWC) ranged from 21.4 to 75.8% and 36.3 to 259.4 mm, respectively. The correlation between soil depth, clay content and PAWC was found significantly correlated (r=0.89**, r=0.89** and r=0.82**, respectively) with yield of tamarind. The soils were slight to strongly alkaline (pH 7.06 to 8.66), non-saline, very low to very high in organic carbon content (0.20 to 1.29%). The CaCO3 increased with depth and slightly to highly calcareous (2.80 to 29.4%). The cation exchange capacity (CEC) of soils varied from 30.0 to 75.1 cmol(p+)kg-1 in different horizons of the pedons. The soils were very low to low in available nitrogen (N) and very low to moderately high in available phosphorus (P), very low to very high in available potassium (K) content and found significant positive correlation with yield (r = 0.92**, r = 0.68** and r = 0.56*, respectively). Whereas, the correlation between CaCO3 and yield of tamarind was found negative (r = -0.012) indicating high amount of CaCO3 in soil reduced the yield of tamarind. Moreover, the relationship between CaCO3 with total soluble solids (TSS) and reducing sugar was found significant positive (r = 0.68** and r = 0.77**, respectively) indicating CaCO3 in soil favour to increasing the sweetness of tamarind fruits. The soils were classified as loamy, smectitic, isohyperthermic, Typic Ustorthents; fine, smectitic, isohyperthermic, Typic Ustorthents; fine, smectitic, isohyperthermic Typic Haplustepts; fine, smectitic, isohyperthermic Calcic Haplustepts; very fine, smectitic, isohyperthermic Calcic Haplustepts; very fine, smectitic, isohyperthermic Typic Haplusterts and very fine, smectitic, isohyperthermic Calcic Haplusterts. The maximum yield and TSS of tamarind (17.09 t ha-1 and 30.21O Brix) was noticed under very fine, smectitic, isohyperthermic Typic Haplusterts and significantly superior over the rest of the soils followed by very fine, smectitic, isohyperthermic Calcic Haplusterts under high management (application of FYM and protective irrigation before flowering). Indicating the application of FYM and protective irrigation to tamarind orchards overcome the adverse effect of CaCO3 and enhance the yield and quality of tamarind.